Internal mass transfer effect on biodegradation of phenol by Ca-alginate immobilized Ralstonia eutropha - Dursun, AY; Tepe, O (Elsevier, 2005)
Phenol biodegradation by free and Ca-alginate immobilized Ralstonia eutropha was performed in batch system. Optimum initial pH and temperature were determined as 7 and 30 degrees C, respectively for free cells, while a wide pH and temperature range were obtained for immobilized cells. Phenol had a strong inhibitory effect on the microbial growth and Haldane model was used to describe the substrate inhibition. Model parameters were determined as mu(max) = 0.89 h(-1), K-S = 55.11 mg dm(-3) and K-1 = 257.94 mg dm(-3) by non-linear regression analysis. The effective diffusion coefficient of phenol in immobilized particles was calculated. For this purpose, using biodegradation rates experimental effectiveness factors were determined for different sized immobilized particles. The Thiele modulus was evaluated from experimental effectiveness factors. Then the average effective diffusion coefficient was calculated as 1.21 x 10(-7) cm(2) s(-1). These results showed that intraparticle diffusion resistance was important for this system and could not be ignored. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; biodegradation; immobilized Ralstonia etaropha; mass transfer; diffusion limitation; effective diffusion coefficients